2012
DOI: 10.7314/apjcp.2012.13.12.6397
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PTEN, VEGF, HER2 and P53 Status in Determining Colorectal Cancer Benefit from Bevacizumab Therapy

Abstract: Background: No factor has thus far been identified to predict the efficacy of bevacizumab therapy for colorectal cancer. We here therefore studied PTEN, VEGF, HER2 and p53 by immunohistochemistry as possible prognostic and predictive factors. Materials and Methods: A total of 34 retrospectively collected tumor samples were evaluated, all from patients receiving bevacizumab-based regimens. VEGF-A, PTEN, HER2, p53 were assessed and data was compared with clinicopathologic characteristics of patients and the beva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…However, this association may not hold true for all tumor types. For instance, benefit from bevacizumab could not be correlated with TP53 status in metastatic colorectal cancer (15,16). On the other hand, these prior studies in colorectal cancer had significant differences in methodology that might have influenced outcome.…”
Section: Resultsmentioning
confidence: 82%
“…However, this association may not hold true for all tumor types. For instance, benefit from bevacizumab could not be correlated with TP53 status in metastatic colorectal cancer (15,16). On the other hand, these prior studies in colorectal cancer had significant differences in methodology that might have influenced outcome.…”
Section: Resultsmentioning
confidence: 82%
“…Previous reports investigating the association between mutational status of p53 and response to bevacizumab were contradictory; some reports showed that p53 status did not affect the efficacy of bevacizumab, 41 , 42 while one report showed that patients with p53-positive (expression) tumors had a significantly longer survival when treated with bevacizumab with chemotherapy; 43 another report showed that the progression-free survival was significantly longer with bevacizumab-containing regimens in patients with mutant p53 tumors, but not in those with wild-type p53 tumors. 44 In the present study, our results show that the three-gene signature is prognostic only in tumors with mutant p53, but not in those with wild-type p53, suggesting that VEGFA -mediated angiogenesis may play an important role in a p53 mutant genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a retrospective analysis compared the PTEN expression (assessed by means of IHC) of 34 tumor samples from patients affected by mCRC treated with bevacizumab-based regimens with treatment activity [35]. No statistically significant differences were found between the response rate and different expression levels of PTEN ( p = 0.832).…”
Section: Pten As a Predictive Factormentioning
confidence: 99%